Multipass spectral broadening of 18 mJ pulses compressible from 1.3 ps to 41 fs - Kaumanns, Martin; Pervak, Vladimir; Kormin, Dmitrii; Leshchenko, Vyacheslav; Kessel, Alexander; Ueffing, Moritz; Chen, Yu; Nubbemeyer, Thomas (Optics letters, 2018)
Nonlinear compression of laser pulses with tens of millijoule energy in a gas-filled multipass cell is a promising approach to realize a new generation of high average power femtosecond sources. For the first time, to the best of our knowledge, we demonstrate nonlinear broadening of pulses with about 18 mJ of energy at a 5 kHz repetition rate in an argon-filled Herriott cell and show compressibility from 1.3 ps to 41 fs. In addition to the large compression factor, the output beam has an outstanding quality and excellent spectral homogeneity. Furthermore, we discuss prospects to scale the energy to the 100 mJ level in the near future.